Increased chemerin and decreased omentin-1 levels in morbidly obese patients are correlated with insulin resistance, oxidative stress and chronic inflammation - CĂTOI, ADRIANA FLORINELA (Clujul Med, 2014)
BACKGROUND AND AIM: Morbid obesity represents a proinflammatory and pro-oxidative state associated with dysregulation of adipokines. We aimed to evaluate the circulating levels of chemerin and omentin-1 in morbidly obese (MO) patients and to investigate the relationship between these two adipokines and between each of them and anthropometric, metabolic, oxidative stress and chronic inflammatory parameters. MATERIAL AND METHODS: 32 MO patients and 20 controls were investigated in this study. Anthropometric, metabolism parameters, inflammatory markers, oxidative stress indicators as well as chemerin and omentin-1 were measured. RESULTS: Serum levels of chemerin were increased while omentin-1 levels were decreased in MO patients when compared with controls. Chemerin correlated positively with insulin, HOMA-IR, LDL cholesterol and negatively with total antioxidant response. Omentin-1 correlated negatively with tumor necrosis factor alpha and total cholesterol. In a multiple linear stepwise regression analysis we learnt that only HOMA-IR (β=0.70, p<0.001), total cholesterol (β=0.42, p<0.001) and triglycerides (β=0.31, p<0.05) remained significantly associated with chemerin changes. Using the same analysis we noticed that total cholesterol (β=−0.71, p<0.001), fasting glucose (β= −0.40, p<0.05) and body mass index (BMI) (β= −0.38, p<0.05) were considered to be significant predictors for omentin-1 changes. CONCLUSIONS: Chemerin and omentin-1 synthesis was dysregulated in MO patients. Chemerin might play a role in insulin resistance and oxidative stress. Chemerin changes seemed to be predicted mainly by insulin resistance. Omentin-1 levels were inversely associated with chronic inflammation and dyslipidemia while the main modulating factors seemed to be dyslipidemia, hyperglycemia and BMI.